A COMPREHENSIVE REVIEW OF HRIDAYA - Shyam Singh. B; Mansoria Poornima; Dadhich O.P. (International Journal of Applied Ayurved Research, 2018)
Ayurveda is a basic science of life having holistic approach. It considers human body composed of Tridosha, Sapta Dhatu, Three Mala and twelve Prana. Hridaya is mentioned as a Pranaytana (resort of life) in Ayurvedic literature which mentions its significance at physiological level to maintain vitality as it functions continuously from birth to death. Hridaya is involved in the flow and conduction of Prana (vital energy in form of Rasa-Rakta) thus it is considered as Pranvaha and Rasavaha Srotas Moola. In Ayurvedic classics it is classified in Shriogata Hridaya and Urogata Hridaya, which indicates the fine association between heart and brain. Hridaya is originated from essence part of Rakta and Kapha Dosha durin 4th month of fetal life. It has immense importance as it is considered as Kosthang, Pratyanga and Marma. Ten vessels (Dash Mahamoola) arise from the Hridaya by which Prana in form of Rasa Rakta and Oja is circulated throughout the body. Rasa Dhatu is circulated from Hridaya to all body under influence of Vyana Vayu result in nourishment of all Dhatus. Thus Hridaya has immense importance in maintaining vitality of an individual.